Empowering special students: Attitudes towards English for communication using "I-Pick" methods - Ahmad, Norizan Saed; Husin, Norshidah Abu; Mustaffa, Fatimah binti (Psychology, Evaluation, and Technology in Educational Research, 2023)
The aim of this study was to identify the attitude of students with special educational needs (MBPK) towards learning based on the I-pick method in English for Communication.  Pictorial Illustration (I-pick) is an innovative teaching method used in this study to improve English vocabulary proficiency among students with special educational needs (MBPK). This study uses the quantitative form of the survey method using questionnaires as an instrument of study. The data was analyzed on a descriptive basis, and the t-test test was used to strengthen the study data. Samples are intended to be used in this study. A total of six MBPK slow learner categories who attended the KSSMPK Form 1 class at SMK Jalan Paya Besar were selected as respondents. The findings showed that MBPK's attitude in the implementation of I-pick-based learning is positive (mean=4). 02, S.D.= 0. 909). This proves that the I-pick method has successfully increased MBPK's interest in learning English for Communication better. Finally, it can be concluded that a positive attitude towards English for Communication learning based on I-pick increased interest and improved English language ability among MBPK.